HUBUNGAN PANJANG DAN BERAT IKAN KEPERAS (Cyclocheilichtyhys apogon) DISUNGAI TELANG DESA BAKAM KABUPATEN BANGKA - Efendiansyah Efendiansyah (Akuatik: Jurnal Sumberdaya Perairan, 2018)
Keperas Fish (Cyclocheilichthys apogon) is one of the dominant species of local fish (indigenous species) found in the waters of Bangka Island. keperas fish has economic value for the people of Bakam village. The purpose of this research is to know the influence of Liquid Waste Disposal Activity of Palm Oil Factory to Fishing Growth (Cyclocheilichtyhys apogon) Telang River Bakam Village in May 2017. Sampling method using purposive sampling. Data analysis used descriptive analysis to know the growth of keperas fish and quantitative analysis to know the value of long correlation weight of male fish (Cyclocheilichthysapogon) in the part before the waste stream follow the equation W = -1.38948L 2.465525 and while for the female fish before the flow of waste W = 0.957107L0.315034 and while the length and weight relationship of male keperas (Cyclocheilichthys apogon) after section of the waste stream follows the equation W = 1.507886L-0.15259 for male keperas fish while for female keperas fish section after the waste stream W = 0 , 580718L0.672259. From the equation we get the value of male fish before the flow of waste of 2.465525 and male fish section after the waste stream of -0.15259, while for the female fish section before the waste stream of 0.315034 and for the female section after the waste flow of 0.672259.